"Les logiques d’intégration et d’appropriation des réponses sociétales par les firmes multinationales. Cas d’étude : Groupe LAFARGE Maroc " - Krombi Abdeslam (Université Mohammed V - Souissi, Faculté des Sciences de l'Education, Rabat, 2019)
In a context characterized by a feeling of lack of confidence in the societal discourse of multinational firms, we sought through this thesis to identify the logic of integration and appropriation of societal responses adopted by the Lafarge Maroc Group, whose parent company to show its interest in societal management since the 1970s. Our research is guided by the following question: What are the motivations behind the Group's societal choice? To answer this question, we have developed a theoretical framework based on the postulates of the neo-institutional approach, those of Carroll's model, as well as on the logic of action proposed by Draetta (2006). The objective of our research and the characteristics of the empirical object have imposed on us the choice of a hybrid epistemological positioning and a complementary methodological posture. Our approach to the subject of research is both exploratory and explanatory. Our working hypothesis is formulated in this way: "the contextual determinants of operationalization influence the decisional choice concerning the integration and the appropriation of societal responses". Our main deliverable is a theoretical model explaining how the contextual determinants of operationalization can constitute a vector of choice for the societal choice of the company.
Keywords: Analyse et évaluation des systèmes d'Education et de Formation; Responsabilité sociétale de l'entreprise (RSE); Réponse sociétale; Déterminant d'implantation; Performance sociale (PSE); Logique appropriation